2020
DOI: 10.1186/s13046-020-01611-0
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of heterogeneous cancer-associated fibroblasts: the molecular pathology of activated signaling pathways

Abstract: Accumulating evidence indicates that intratumoral heterogeneity contributes to the development of resistance to anticancer therapeutics. Fibroblasts, which are components of the paraneoplastic stroma, play a crucial role in the wound-healing process. Activated fibroblasts accumulate in the wound and are involved in many aspects of the tissue remodeling cascade that initiates the repair process and prevents further tissue damage. The pathophysiological roles of cancer-associated fibroblasts (CAFs) in the hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
146
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(163 citation statements)
references
References 146 publications
1
146
3
Order By: Relevance
“…Thus, whilst naïve SFs display hypermethylation of the promoter and TSS regions of genes associated with regulation of pluripotency and (oncofetal) development, many of these sites are hypomethylated and potentially derepressed in CIA-, but not ES-62-CIA-, SFs. By contrast, whilst elements associated with the FoxO, Hippo and Wnt signalling pathways that are key to the regulation of these processes (stem cell biology, cilia and intercellular communication, organ development, immunomodulation, tissue repair and regeneration and ageing 64, 84, 85 ) are similarly hypomethylated in CIA SFs and hypermethylated in ES-62-CIA, these genes are also hypomethylated in naïve SFs. Of related interest, we have previously shown ES-62 to strongly induce negative regulators (WIF1, AMOTL2 and CRYBB2) of Wnt signalling in RA synovial membranes, in vitro 86 .…”
Section: Discussionmentioning
confidence: 92%
“…Thus, whilst naïve SFs display hypermethylation of the promoter and TSS regions of genes associated with regulation of pluripotency and (oncofetal) development, many of these sites are hypomethylated and potentially derepressed in CIA-, but not ES-62-CIA-, SFs. By contrast, whilst elements associated with the FoxO, Hippo and Wnt signalling pathways that are key to the regulation of these processes (stem cell biology, cilia and intercellular communication, organ development, immunomodulation, tissue repair and regeneration and ageing 64, 84, 85 ) are similarly hypomethylated in CIA SFs and hypermethylated in ES-62-CIA, these genes are also hypomethylated in naïve SFs. Of related interest, we have previously shown ES-62 to strongly induce negative regulators (WIF1, AMOTL2 and CRYBB2) of Wnt signalling in RA synovial membranes, in vitro 86 .…”
Section: Discussionmentioning
confidence: 92%
“…By constructing a 3D collagen invasion model, Wei et al showed that CAAs remodeled collagen alignment concerning of PAI-1 or PLOD2 up-regulation during crosstalk with BC cells in vitro and in vivo, further boosting BC metastasis [80]. It is worth noting that the increased matrix stiffness, which can be sensed by many cell types, is a feature of most solid tumors [86]. Yes-associated protein (YAP) function is essential to establish and maintain the tumor-promoting function of CAFs, including stromal sclerosis, invasion and angiogenesis.…”
Section: Extracellular Matrix Remodelingmentioning
confidence: 99%
“…It has been reported that the Hippo pathway can be activated by stromal stiffness in solid tumor tissues, and central to this signaling is a kinase cascade leading from the tumor suppressor Hippo to the oncogenic Yki (YAP/TAZ in mammals), which is a transcriptional coactivator of target genes involved in cell proliferation and survival [88]. In addition, YAP is activated in CAFs in response to mechanical stress, perturbation of the actin cytoskeleton and ECM stiffness [86,87]. Besides, the increased expression of YAP in preadipocytes is correlated with the repression of adipogenic differentiation processes [89].…”
Section: Extracellular Matrix Remodelingmentioning
confidence: 99%
“…The PLX4720 has an effect on the tumor stroma and promote matrix production, ECM remodeling leading to activation of integrin β1/focal adhesion kinase (FAK)/Src and ERK signaling. Melanoma-associated fibroblasts activate paradoxically adhesion-mediated signaling, which supports residual disease, result in enhancing the population of cancer cells [20,58,59]. Activating mutations in kinase PI3K/AKT have been reported that increase AKT activity, promoting melanoma and resistance to apoptosis [60].…”
Section: Genetic Analysis Of Huvec Differentiation Into Caf By Both Ementioning
confidence: 99%
“…EndMT contributes to the accumulation of CAFs and most CAFs are formed by EndMT [18]. For example, with regard to the omental tumor microenvironment, omental fibroblasts are trans-differentiated from adipose-derived mesenchymal stem cells by ovarian cancer-derived exosomes and are associated with transforming growth factor beta (TGF-β) signaling secreted by both cancer cells and stromal cells [19,20]. TGF-β contributes to recruiting stromal cell types characterized by CAFs, inducing ECM production and downregulating the expression of ECM-associated protease [21].…”
Section: Introductionmentioning
confidence: 99%